Analisis Kebutuhan Pengembangan Bahan Ajar Keterampilan Membaca di SMK Bhinneka Karya Surakarta - Atmojo, Danang Tri, Laili Etika Rahmawati, S.Pd., M.Pd (2016)
This research had two goals who want to study. (1) Description of the profile of teaching materials of reading skills used in SMK Bhinneka Karya Surakarta. (2) Description needs teachers and students on the development of teaching materials of reading skill Semenjana level that is in SMK Bhinneka Karya Surakarta. The type of research is qualitative descriptive. Design research used is a case study. Technique data collection used in this research is study documents, interview and chief. The results of this research are as follows. (1) The profile of teaching materials of reading skill used in SMK Bhinneka Karya Surakarta has been good enough but also needs development of teaching materials of the use of the text that in accordance with their interests students. (2) Needs teachers and students related development of teaching materials of reading skill consisting of the said need of the development of teaching materials skill reading in accordance with their interests students, while students having any interest to read related the text sports.